ANALISIS PENGARUH PDRB, JUMLAH PENDUDUK, JUMLAH INDUSTRI, DAN BELANJA DAERAH TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN/KOTA PROVINSI JAWA BARAT 2017-2021 - Gunawan Bayi Aji (Jurnal AKTUAL, 2023)
This study reveals the results of a study that analyzes the factors that affect Regional Original Income (PAD) on Gross Regional Domestic Product (GRDP), Number of Industries, Number of Population and Regional Expenditure of West Java Province (2017-2021 period) with the variables used are PAD, GRDP, Number of Industries, Number of Population and Regional Expenditure. The purpose of this study is to determine the extent of the influence of GRDP, the number of industries, the number of population and regional expenditures on PAD. This study uses three methods, namely Common effect model, Fixed effect model and Random effect model through Chow Test, Hausman Test, coefficient of determination, f test, t test. The study found that the results of statistical testing turned out to be all in favor of the existing  hypothesis. That the variables of GRDP, number of industries, population and regional expenditure have a significant effect on PAD. Keywords : Regional Native Food, GRDP, Number of Industries, Number of Population, Shopping Area.